Screening and Characterization of Onion Ecotypes for Resistance to Purple Blotch Disease in Sudan Savannah - Adigari, J. J.; Mohammed, I. U.; Muhammad3, A.; Akibu, M. M; Yusuf, I. J (Darul Yasin Al Sys, 2025)
Field experiment was conducted during 2023/2024 dry season at Teaching and Research Orchard of Kebbi State University of Science and Technology, Aliero and Teaching and Research Farm of Usmanu Danfodio University, Sokoto at Kwalkwalawa using twelve (12) local onion ecotypes (Ex-Dikwa, Ex-Kaffe, Ex-Bama, Ex-Aliero, Ex-Gothege, Ex-Gada, Ex-Wurno, Ex-GHM, Ex-Gaya, Ex-Borno, Ex, Lahodu and Ex-Goronyo). Factorial combination of inoculation were allocated on the main plot while ecotypes on the sub-plot and replicated three times in Randomized Complete Block Design (RCBD). The size of each plot was 1x2m (2m2) with aim of screening and characterization of these ecotypes for their resistance to purple blotch disease caused by fungus Altenaria porii, where none of the ecotypes were found immune. However, based on the PDI result, the ecotypes Ex-Dikwa (19.53, 18.65), Ex-Kaffe (17.83, 19.21) and Ex-Borno (18.59, 18.32) were found to be moderately resistant to purple blotch disease. Ex-Bama (32.27, 34.27), Ex-Gothege (41.89, 40.78), Ex-Wurno (37.92, 36.82) and Ex-Goronyo (32.60, 34.50) were found to be moderately susceptible, while Ex-GHM (52.51, 51.43), Ex-Gaya (54.39, 56.39) and Ex-Lahodu (43.77, 41.57) were susceptible to purple blotch in Aliero and Sokoto respectively. Similarly, growth and yield parameters measured during this research work, such as plant height, leaf number, total biomass, above ground biomass, fresh bulb yield, cured bulb yield, bulb diameter characterized Ex-Dikwa, Ex-Kaffe and Ex-Borno as superior compare to other ecotypes, with Ex-Lahodu, Ex-GHM and Ex-Goronyo recording lower in growth and yield performance. The identified moderately resistant ecotypes can further be used for commercial cultivation or may be used as parent for future onion improvement program against purple blotch disease.